Kontribusi Sosial Ekonomi Orang Tua, Motivasi DanSarana Pembelajaran Terhadap Kemandirian Dan Dampaknya Pada Hasil Belajar Kimia Kelas X Mia Man 2 Sragen - sugiyo, sugiyo, Dr. Sumardi, M.Si, Dr. Eko Supriyanto (2016)
This research aims to test 1) contribution economic social of parent, motivate, kids of study and independence to result learn by simultan and also by partial2) contribution economic social of parent, motivation and medium of study to independence by simultan and also by partial, 3) contribution independence to result learn the student of class of X MIA in MAN 2 Sragen Research type is research survey by desain in correlational population in this research the chemistry of student of class of X MIA in MAN 2 Sragen with the amount 120. Sample in this research amount to 92 students selected by using technique of random sampling. Data collecting with the technique of quetionnare and documentation of result of learning. Technique analysis the data by using technique analysis two band.Result of analysis conclude that 1) contribution economic social of parent, motivate the, kids of study and independence to result learn the chemistry of student of class X MIA in MAN 2 Sragen by simultan and also partial proven by its truth. This matter is shown with the examination result test F and test t statistic; 2) contribution economic social of parent, motivate and study medium to independence in class of X MIA in MAN 2 Sragen by simultan or partial proven by its truth is this matter is shown with the examination result test F and test t; 3) independence of have contribution of significan to result learn the chemistry of student of class of X MIA in MAN 2 Sragen Keyword : result learn, independence, economics social of parent, motivate, study medium.